Numerical simulation of composite armor subjected to ballistic impact. (2019) - NayanPundhir,; Goyal, Deepak; Singh, Pradyut; Pathak, Himanshu; Zafar, Sunny
Abstract: Composite materials are widely used in the engineering field due to their high strength-to-weight ratio which offers enhanced mechanical behaviour of the components. Some of the widely used fields for the composite materials are body armors, safety shoes, sports and in many other regions. In this paper ballistic impact simulation of composite plate of Ultra high molecular weight polyethylene (UHMWPE) and alumina is done using ANSYS-AUTOYN 16.0. For analysing the behaviour of the composite plate the impact velocity is varied in steps and is directed perpendicularly on to the surface of the plate. Here three cases have been studied, in the first case UHMWPE as front plate of UHMWPE/Alumina composite has been considered for the impact whereas in second case alumina is used as the front plate of the impact and in the third case UHMWPE is alone used as the impact plate.